Mechanisms and modelling approaches to weight loss in fresh fruit: a review - Robert Lufu; Alemayehu Ambaw; Umezuruike Linus Opara (Technology in Horticulture)
The symptoms of fruit weight loss are common, including but not limited to shrivelling, changes in product colour, textural properties, total soluble solids, product flavour and saleable weight. However, fruit weight loss is a complex process involving the interaction of product morphology, physiology, and environmental influence. Fruit is hierarchically structured and has features that extend from the molecular scale level to the food plant scale and yet water transport occurs at different spatial scales including nanoscale, microscale, mesoscale and macroscale. Therefore, the modelling of water loss in fresh fruit has been done using micro, macro and multiscale approaches. This review aims to provide a detailed scientific understanding of the interaction between the mechanisms of weight loss and the water loss modelling approach in fresh fruit.